An attachment‐based program for parents of youth with clinically significant mental health problems: Scaling up and drilling down to mechanisms of change - Marlene M. Moretti; Sebastian P. Dys; Stephanie G. Craig; Carlos A. Sierra Hernandez; Natalie Goulter; Katherine O’Donnell; Dave S. Pasalich (JCPP Advances)
Abstract Background Given the prevalence and recent increases in youth mental health problems, there is a pressing need for interventions that target transdiagnostic protective factors that could be targeted as mechanisms of change in treatment. Such interventions are most likely to succeed in meeting population needs if they are scalable, sustainable, and effective. Connect is a manualized, 10‐session trauma‐informed and attachment‐based parent program that is structured, emotion‐focused and skills‐oriented. Developed for broad implementation by community mental health workers, Connect is designed to promote parent–child attachment security, a well‐established transdiagnostic protective factor for youth mental health. Methods We examined whether parent–youth attachment anxiety and avoidance predicted reductions in internalizing and externalizing problems in a large one‐group clinical sample of youth (N = 527; ages 8–18 years) of parents (N = 690) who completed the Connect program in a longitudinal study with 6 time points (pre‐, mid‐, and post‐treatment; 6‐, 12‐ and 18‐month follow‐up). Results Findings confirmed that parent and youth reports of attachment anxiety and avoidance, as well as internalizing and externalizing problems, significantly declined over the course of the intervention. Parent reported reductions in youth attachment anxiety, but not avoidance, predicted declining levels of youth internalizing problems. As well, parent reported reductions in youth attachment avoidance and anxiety predicted declining youth externalizing behavior. In contrast, youth reports of reductions in youth attachment anxiety, but not attachment avoidance, were associated with declines in youth externalizing problems. Conclusion Our findings support the role of attachment as an important transdiagnostic mechanism of change in attachment‐based programs for parents of teens with clinically significant mental health problems.